2017
DOI: 10.1002/jwmg.21282
|View full text |Cite
|
Sign up to set email alerts
|

Winter habitat associations of eastern spotted skunks in Virginia

Abstract: Eastern spotted skunk (Spilogale putorius) populations have declined throughout much of their range in the eastern United States over recent decades. Declines have been attributed to habitat loss or change, increased competition with sympatric mesocarnivore species, or disease. To better understand the extant distribution of spotted skunks in the Appalachian Mountains of western Virginia, USA, we used a detection‐non‐detection sampling approach using baited camera traps to evaluate the influence of landscape‐l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
33
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 52 publications
3
33
1
Order By: Relevance
“…Between January and April 2016 we surveyed 18 sites continuously for 3 months, and between January and April 2017 we surveyed 27 sites continuously for 3 months. Recent detections of spotted skunks in the Appalachian Mountains have been primarily limited to higher elevation (>350 m) sites (Diggins et al , Wilson et al 2016, Thorne et al ), we therefore selected sites that were stratified by elevation to capture potential differences in topographic or vegetative conditions associated with elevation. We then created random points within our 5 elevational strata such that sampling points were ≥1.5 km from each other.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Between January and April 2016 we surveyed 18 sites continuously for 3 months, and between January and April 2017 we surveyed 27 sites continuously for 3 months. Recent detections of spotted skunks in the Appalachian Mountains have been primarily limited to higher elevation (>350 m) sites (Diggins et al , Wilson et al 2016, Thorne et al ), we therefore selected sites that were stratified by elevation to capture potential differences in topographic or vegetative conditions associated with elevation. We then created random points within our 5 elevational strata such that sampling points were ≥1.5 km from each other.…”
Section: Methodsmentioning
confidence: 99%
“…Directed investigations of habitat associations of eastern spotted skunks are generally sparse, and strong predictors of occurrence have yet to be identified. One recently completed study from the central Appalachian Mountains in Virginia, USA, indicated that eastern spotted skunk occurrence is influenced by a combination of forest stand age and elevation (Thorne et al ). Specifically, within occupied landscapes, eastern spotted skunks appear to prefer younger pine forests or mature deciduous forests, presumably because of the increased understory complexity these forest types offer at their respective stages of growth (Lesmeister et al , Thorne et al ).…”
mentioning
confidence: 99%
See 3 more Smart Citations